If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3 = x/(-3)-1 // - x/(-3)-1
1-(x/(-3))+3 = 0
1/3*x+4 = 0 // - 4
1/3*x = -4 // : 1/3
x = -4/1/3
x = -12
x = -12
| 2*(7/4)^2-7(7/4)-4 | | 15=7x-5(2x+3) | | 39=3(x+2) | | -3n-4+2n=-27 | | 29+12x=173 | | 198=-6(-6-3) | | 12x-20=-4x-16 | | 8k+12=52 | | -7x-28=-98 | | (2x-6)(2x-3)=0 | | 157*=2 | | log[3](2x+1)=2 | | 2xy^2-6x-3y=0 | | 12m^3-6m^2+3m= | | 3x=sqr(6) | | 3x=sqrt(6) | | 30=223/x | | -7x-11=16-8x | | Y^2=6y-9 | | 6(2x+1)=1 | | 18a^2b+27ab^2= | | -140=-5x+5(3x-16) | | 10-x=3x+24 | | 1x+1=2x-8 | | x^2-0.00469x+0.0002345=0 | | 12x^3y^4-39x^4y^3= | | -31-5x=15-7x | | 3-x=x^2+15 | | 2g+3=5 | | -4(5y-6)+2(3y+8)= | | .3x+.4=.5x-.8 | | 3x-6+2x+11=45 |